Techno environmental assessment of Flettner rotor as assistance propulsion system for LH2 tanker ship fuelled by hydrogen - Alkhaledi, Abdullah N. F. N. R.; Sampath, Suresh; Pilidis, Pericles (Elsevier, 2023)
This study presents a novel design and development of a 280,000 m3 liquefied hydrogen tanker ship by implementing a set of 6 Flettner rotors as an assistance propulsion system in conjunction with a combined-cycle gas turbine fuelled by hydrogen as a prime mover. The study includes assessment of the technical and environmental aspects of the developed design. Furthermore, an established method was applied to simulate the LH2 tanker in different voyages and conditions to investigate the benefits of harnessing wind energy to assist combined-cycle gas turbine in terms of performance and emission reduction based on engine behaviour for different voyages under loaded and unloaded, normal as well as 6 % degraded engine, and varying ambient conditions. The results indicate that implementing a set of 6 Flettner rotors for the LH2 tanker ship has the potential to positively impact the performance and lead to environmental benefits. A maximum contribution power of around 1.8 MW was achieved in the winter season owing to high wind speed and favourable wind direction. This power could save approximately 3.6 % of the combined-cycle gas turbine total output power (50 MW) and cause a 3.5 % reduction in NOx emissions.
Keywords: Liquefied hydrogen; LH2 tanker mission; Renewable energy; LH2 tanker Performance; Flettner rotors; Environmental